2018
DOI: 10.2134/agronj2017.07.0398
|View full text |Cite
|
Sign up to set email alerts
|

Dryland Corn and Grain Sorghum Yield Response to Available Soil Water at Planting

Abstract: A gronomy J our n al • Volume 110 , I ssue 1 • 2 018 W ater availability at critical growth stages of crops is the major yield limiting factor in dryland crop production (Farahani et al., 1998;Allen, 2012). Dryland agriculture is a special case of rainfed agriculture practiced in arid and semiarid regions. In these regions when irrigation is not used, water conservation becomes the primary focus of management decisions because growing season precipitation is seldom suffi cient to fully meet evapotranspiration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
(47 reference statements)
0
20
0
1
Order By: Relevance
“…Reduced heat stress and enhanced soil water availability due to above-average precipitation may have increased grain yield in these years. Dryland corn grain yield responds linearly to available soil water from precipitation and irrigation (Nielsen et al, 2010;Schlegel et al, 2018). Increased grain yield compared with biomass increased harvest index in 2006, 2009, and 2010 when air temperature and precipitation were favorable for corn growth compared with other years.…”
Section: Tillage System †mentioning
confidence: 99%
“…Reduced heat stress and enhanced soil water availability due to above-average precipitation may have increased grain yield in these years. Dryland corn grain yield responds linearly to available soil water from precipitation and irrigation (Nielsen et al, 2010;Schlegel et al, 2018). Increased grain yield compared with biomass increased harvest index in 2006, 2009, and 2010 when air temperature and precipitation were favorable for corn growth compared with other years.…”
Section: Tillage System †mentioning
confidence: 99%
“…The fallow phase of the production system is critical for conservation of soil water that stabilizes wheat yields and prevents crop failure in drier years in NT regions of the semiarid Great Plains (Haas et al 1974;Nielsen and Vigil 2010). In this water-limited environment, crop yields are directly related to available soil moisture at time of cash crop seeding (Schlegel et al 2018). Despite the weed-suppression benefits of CCs, previous research demonstrated that replacing fallow with CCs often resulted in decreased soil water content at time of cash crop seeding (Holman et al 2018;Nielsen and Vigil 2018;Schlegel and Havlin 1997;Unger and Vigil 1998;Zentner et al 1996).…”
Section: Soil Moisture Trade-offs and Impacts On Cash Crop Yieldsmentioning
confidence: 99%
“…), and chick pea (Cicer arietinum L.) have replaced a portion of this fallow period in the northern parts (Miller et al 2003). Similarly, several new crops have been evaluated in 3-or 4-yr rotation schemes by including cereal crops (Nielsen and Vigil 2018;Schlegel et al 2018), legumes as forage and grain crops (Holman et al 2018;Lyon et al 2004), and recently oilseed crops (Obour et al 2018) for potential replacement of fallow in the Central Great Plains (Figure 1). Despite these efforts to increase cropping intensity, crop rotations in the region still include a fallow phase, and most growers practice fallow as a strategy to minimize risk of drought and crop failure.…”
Section: Introductionmentioning
confidence: 99%
“…Bushong et al reported the impact of preplant irrigation on phosphorus and potassium fertilizer management in winter wheat with grain yield and water productivity optimized under preplant irrigation condition [35]. Schlegel et al found an increase in rainfed maize grain yield from 27 to 33 kg/ha/mm of pre-plant irrigation when in-season precipitation ranged from 196 to 215 mm and yield decrease from 9 to 25 kg/ha/mm when the in-season precipitation ranged from 288 to 354 mm under increasing preplant irrigation amounts (0, 38, 76, or 114 mm) at two locations in Kansas [36]. Rainfed grain sorghum yield also increased with increasing preplant irrigation amounts from 12 to 22 kg/ha/mm and from 0 to 6 kg/ha/ mm under in-season precipitation ranges of 163 -281 mm and 315 -382 mm respectively [36].…”
Section: Effect Of Preplant Irrigation On Crop Yields and Water Use Ementioning
confidence: 99%
“…Schlegel et al found an increase in rainfed maize grain yield from 27 to 33 kg/ha/mm of pre-plant irrigation when in-season precipitation ranged from 196 to 215 mm and yield decrease from 9 to 25 kg/ha/mm when the in-season precipitation ranged from 288 to 354 mm under increasing preplant irrigation amounts (0, 38, 76, or 114 mm) at two locations in Kansas [36]. Rainfed grain sorghum yield also increased with increasing preplant irrigation amounts from 12 to 22 kg/ha/mm and from 0 to 6 kg/ha/ mm under in-season precipitation ranges of 163 -281 mm and 315 -382 mm respectively [36]. Stone, et al investigated the timing of off-season irrigation in maize in Kansas and found that offseason irrigation timing did not significantly impact maize yield and concluded that off-season irrigation of maize was not a water efficient practice [20].…”
Section: Effect Of Preplant Irrigation On Crop Yields and Water Use Ementioning
confidence: 99%